1975
DOI: 10.1093/nar/2.11.2163
|View full text |Cite
|
Sign up to set email alerts
|

Low-angle neutron scattering from chromatin subunit particles

Abstract: Monomer chromatin particles containing 140 base pairs of DNA and eight histone molecules have been studied by neutron scattering. From measurements in various H20/D20 mixtures, radii of gyration and the.-average scattering density.of the particle were determined. The radius of gyration under conditions when scattering from the DNA dominates is 50A, and when scattering from the protein dominates, 30A. Consequently the core of the particle is largely occupied by the histones while the outer shell consists of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(57 citation statements)
references
References 23 publications
6
50
0
Order By: Relevance
“…As predicted in our model, the DNA was found to be on the outside (see Pardon et al, 1975). The ubiquity of nucleosomal structure among eukaryotes was clearly established by Dennis Lohr's demonstration of nucleosomes in yeast (Lohr & van Holde, 1975).…”
supporting
confidence: 73%
“…As predicted in our model, the DNA was found to be on the outside (see Pardon et al, 1975). The ubiquity of nucleosomal structure among eukaryotes was clearly established by Dennis Lohr's demonstration of nucleosomes in yeast (Lohr & van Holde, 1975).…”
supporting
confidence: 73%
“…Subunits from higher eukaryotes contain two copies each of histones H2A, H2B, H3, and H4 associated with about 140 base pairs of DNA (12,14). Recent neutron diffraction studies (15) have confirmed earlier proposals (10,11) that these histones form a "core" about which the unit length of DNA is wrapped. Lysine-rich histones HI (and H5 in erythrocytes) appear to be associated primarily with the "spacer" DNA, 30-60 base pairs long, between globular subunits (14,16,17).…”
mentioning
confidence: 82%
“…A well-characterized entity within the basic subunit of chromatin, the nucleosome, is the "core particle," which has a molecular weight of 200,000 and contains approximately 140 base pairs of DNA and two molecules each of the histones H2A, H2B, H3, and H4 (1,2). Electron microscopy (3,4), neutron scattering (5,6), and x-ray diffraction (7) studies indicate that the "core particle" is a disk 110 A wide by 55 A high with two turns of DNA localized around the compact histone center. The arrangement of histones in the center and along the DNA within a nucleosome is not known.…”
mentioning
confidence: 99%